Fundamentals of Corporate Finance - Parrino, Robert, 1957-, author 528636; Bates, Thomas W., author 643487; Gillan, Stuart L., author 413860; Kidwell, David S. , author 190765 (Hoboken, NJ : John Wiley & Sons, Inc., 2022)
"This book is more than a collection of ideas, equations, and chapters. It has an important integrating theme-that of value creation. This theme, which is carried throughout the book, provides a framework that helps students understand the relations between the various concepts covered in the book and makes it easier for them to learn these concepts. The concept of value creation is the most fundamental notion in corporate finance. It is in stockholders' best interests for value maximization to be at the heart of the financial decisions made within the fi rm. Thus, it is critical that students be able to analyze and make business decisions with a focus on value creation. The concept of value creation is introduced in the first chapter of the book and is further developed and applied throughout the remaining chapters. The theme of value creation is operationalized through the net present value (NPV) concept. Once students grasp the fundamental idea that financial decision makers should only choose courses of action whose benefits exceed their costs, analysis and decision making using the NPV concept becomes second nature. By helping students better understand the economic rationale for a decision from the outset, rather than initially focusing on computational skills, our text keeps students focused on the true purpose of the calculations and the decision at hand"-- Provided by publisher